Empirical Analysis of Racial Disparities in Policing - Deepak Premkumar; Magnus Lofstrom; Joseph Hayes; Brandon Martin; Sean Cremin (Institute of Labor Economics (IZA), 2025)
Racial disparities within the criminal justice system continue to be a pressing issue in the U.S. In this paper, we analyze data for almost four million stops by California's fifteen largest law enforcement agencies in 2019, examining the extent to which people of color experience searches, enforcement, intrusiveness, and use of force differently from white people. Black Californians are more likely to be searched than white Californians, but searches of Black civilians reveal less contraband and evidence. Black people are overrepresented in stops not leading to enforcement as well as in stops leading to an arrest. While differences in location and context for the stop significantly contribute to racial disparities, notable inequities remain after accounting for such factors. These disparities are concentrated in traffic stops. A notable proportion of which lead to no enforcement or discovery—suggesting that gains in efficiency and equity are possible. Through a "veil of darkness" analysis, we find evidence that racial bias may be a contributing factor to disparities in traffic stops for Black and Latino drivers. These findings suggest that traffic stops for non-moving violations deserve consideration for alternative enforcement strategies.
Keywords: J15; K42; K14; H41; 330; policing; racial disparities; racial bias; stops; searches; enforcement